Dampak Program Bantuan Stimulan Perumahan Swadaya (BSPS) Terhadap Peningkatan Kesejahteraan Ekonomi Masyarakat di Desa Pule - Firdaus, Elsa Alfionita; Huda, Syamsul; Utami, Anisa Fitria (Jurnal Ilmiah Wahana Pendidikan, 2023)
Community welfare can be realized if basic needs such as clothing, food and shelter can be fulfilled. However, welfare is not only seen from the fulfillment of food needs. The need for housing is an important factor that needs attention. Limitations of the community in meeting the needs of adequate housing have resulted in many people having inadequate housing. Access to proper housing can be influenced by low economic factors in the community and high poverty. This study aims to determine the impact of the Self-Help Housing Stimulant Assistance (BSPS) program in Pule Village, Pule District, Trenggalek Regency on increasing the economic welfare of the community. The method used in this research is a qualitative method with a descriptive type of research, in which data collection is carried out using in-depth interviews with beneficiaries, field observations, and data sourced from the Central Statistics Agency (BPS) and related agencies. The results showed that the BSPS program had a very influential impact on increasing the economic welfare of beneficiaries, builders and workers, as well as providers of building materials in Pule Village. In addition to increasing economic welfare, beneficiaries are also assisted in having proper housing in accordance with the provisions of Livable Houses (RLH). The community in Pule Village hopes that the BSPS program can be implemented again so that the community can obtain proper housing and be able to increase economic welfare.